TIKTOK AND MENTAL ILLNESS - Weni Prinata; Venesa Carolina, Nacha Enjelika, Septia Monica, Nova Lady Simanjuntak (Jurnal Kesehatan, 2024)
Mental health is health related to the emotional, mental and psychological state of a person. Keep in mind that life events that have a significant impact on a person's personality and behavior can also affect their mental health. This research aimed to look at the relationship between the use of Tik Tok social media and mental health in its users. There was significant relationship between the use of Tik Tok social media and the mental health of its users. Social media usage could be an option to prevent or cope with stress. However, social media usage has to be done responsibly so as not to cause dependence. Self-awareness and regulation of TikTok use are key in managing the potential impact on mental health. Policymakers, social media platforms and parents need to work together to create a healthy online environment and support the positive development of TikTok users' mental health. As such, this study provides better insight into the complex relationship between TikTok use and mental health, while emphasizing the need for a holistic approach to promote users' well-being.